PENYULUHAN MANFAAT YOGA SEBAGAI UPAYA MENGURANGI DISMENOREA - Nugrawati, Nelly; Ekawati, Nur; Wijaya, Ayu; Muhammad Adam, Andi (Stikes Yarsi Mataram, 2025)
Yoga has been proven effective in helping reduce dysmenorrhea (menstrual pain) in adolescent girls by enhancing muscle relaxation, blood circulation, and hormonal balance. Proper yoga techniques can alleviate muscle tension and improve flexibility, which may help relieve pain and discomfort during menstruation. This community service activity aims to provide education and counseling on the benefits of yoga as a non-medical approach to reducing dysmenorrhea for students at SMAN 1 Pangkep Makassar. The methods used in this activity include counseling, demonstrations of yoga poses, and joint practice sessions guided by an experienced yoga instructor. Student participation was documented and evaluated to measure their increased understanding of yoga and its effects on menstrual pain. The results of this activity showed that 85% of participants reported a decrease in pain intensity after regularly practicing the yoga poses taught, compared to their condition before the training. This counseling successfully improved students’ knowledge and skills in managing dysmenorrhea through yoga and encouraged them to take better care of their health. Thus, this counseling not only provides a practical solution for students in addressing menstrual pain but also has the potential to enhance the quality of life and well-being of adolescent girls in school and community environments